Eosinophilic esophagitis and anaphylaxis due to cow's milk in an infant - Topal, Erdem; Eğritaş, Ödül; Arga, Mustafa; Sarı, Sinan; Poyraz, Aylar; Bakırtaş, Arzu; Dalgıç, Buket (The Turkish Journal of Pediatrics, 2013)
Food allergies are often seen in infancy and usually show the clinical signs in the form of type I hypersensitivity reaction. However, a combination of food allergies can sometimes be found in the same patient. In this report, we present an 11-month-old infant who had a combination of anaphylaxis and eosinophilic esophagitis induced by cow's milk. Diagnosis of eosinophilic esophagitis is done by examination of esophageal biopsy material histologically. This is a very rare combination of food allergy. Improvement in clinical and histological findings of eosinophilic esophagitis was achieved by removal of cow's milk and dairy products from the infant's diet.